A statistical damage constitutive model considering whole joint shear deformation. (June 2020) - Xie, Shijie; Lin, Hang; Wang, Yixian; Chen, Yifan; Xiong, Wei; Zhao, Yanlin; Du, Shigui
The whole shear deformation of rock joints significantly affects the long-term behavior and safety of engineering projects. In this paper, a new damage constitutive model related to the Weibull distribution and statistical damage theory is proposed. This model considers the shear stiffness degradation, post-peak softening, and residual phase of rock joints in the whole shearing process. Main works include the three following aspects: First, the phase of initial damage is determined on the assumption that the joint shear failure is regarded as a result of damage evolution, according to the typical joint shear curve and the three-parameter Weibull distribution. Then, a statistical damage evolution model for the whole joint shearing process is introduced to make this model be capable of describing the residual phase of rock joints. Finally, a statistical constitutive model for the whole joint shearing process is proposed by statistical damage theory, and the calculated results of the models are compared to the experimental results. The results indicate that the proposed model shows a good agreement with the experimental examples, and the proposed model can distinctly reflect the effects of residual stress, peak stress, and shear stiffness. In addition, the model parameters can be mathematically confirmed and have distinct physical meanings.